Ideology Takes a Day Off: Althusser and Mass Culture - Chip Rhodes (Studies in 20th & 21st Century Literature, 1994)
As theories of mass culture that focus on empowerment, use value and utopian bribes have become increasingly popular, Althusser's groundbreaking work on structural causality and ideology has been left aside because of its alleged inability to account for social resistance. This is unfortunate because such Althusserian concepts still provide the most productive foundation for a Marxist approach to mass culture that avoids both unwitting apologetics and facile, ethical critiques. Nevertheless, many of Althusser's theoretical claims are in need of revision. As the film Ferris Bueller's Day Off implicitly suggests, Althusser's distinction between ideology and the aesthetic no longer holds in consumer-oriented capitalism. In addition, the film undermines Althusser's assertion that the schools are the most powerful ISA under capitalism, suggesting instead that mass culture now fulfills this function under late capitalism. Moreover, this reshuffling of the ideological hierarchy necessarily produces a fresh set of concrete, historically specific contradictions. These contradictions, in turn, provide new possibilities for resistance and social change.
Keywords: theories of mass culture; mass culture; empowerment; utopian bribes; value; Althusser; structural causality; ideology; social resistance; Althusserian concepts; Marxist approach; Marxism; ethical critiques; Ferris Bueller' s Day Off; film; aesthetic; consumer-oriented capitalism; capitalism; school; ISA; late capitalism; ideological hierarchy; contradictions; resistance; social change